Igreja Evangélica Reformada no Brasil em Castrolandia: religião, educação e trabalho em uma colônia holandesa: um estudo de caso - Lucena, Wilson de Lima (2009)
The Reformed Evangelical Church in Brasil in Castrolanda, object of this study, is composed in its majority, for dutches and descendants, and it demonstrates to be detainer of the religious and partner-cultural preservation of the dutch remodelled ones. The cause of dutch immigration is finds in the growth of the population, little territorial area and the consequences of World War II in the Europe and, at the same time, the easinesses of immigration offered by countries as Brazil. Having as subject of this research the Reformed Evangelical Church in Brasil in Castrolanda - Religion, education and work in a dutch colony - A case study , we demonstrate as the religiousity walked in set with this dutch ethnic group, being factor of aggregation and motivation for linguistic and cultural permanence, beyond being instrument for creation and maintenance of an educational ideal and of work, that success sufficiently gets until our days.